Determination of Diazinon in Fruits from Northeast of Iran Using the QuEChERS Sample Preparation Method and GC/MS - Akhlaghi, Hashem; Motavalizadehkakhky, Alireza; Emamiyan, Reyhane (Asian Journal of Chemistry, 2012)
The aim of this study was to identify pesticide residues found in cultivated fruits from northeastern Iran during 2011, using the QuEChERS method prior to analysis by GC/MS. Selected fruits were apples, grapes, melons, watermelons and cherries that had been sprayed twice with the organophosphorus pesticide, diazinon, during growth. In 75 samples the mean concentration of diazinon ranged from 0.11 to 0.88 mg/kg. The mean level of diazinon in apple samples was below the maximum residue limit recommended by world health and food and agricultural organizations, while the mean levels of diazinon in grapes, melons, watermelons and cherries exceeded the maximum residue limits. These results provide information on the status in one agricultural area in Iran and point to the necessity of controlling the use of some excessively applied and potentially persistent organophosphorus pesticides.